Risk Factors Associated with Maternal Mortality in Donggala Regency, Indonesia: Evidence from a Case–Control Study (2020–2024) - Tri Rizkiyanti alwi; Sudirman Sudirman; Zhanaz Tasya (Journal of Public Health Indonesian, 2026)
Maternal mortality remains a significant public health problem and reflects the quality of maternal health services. Donggala Regency is one of the regions with a relatively high and fluctuating maternal mortality rate during the period 2020–2024. This study aimed to analyze risk factors and determine the most influential factors associated with maternal mortality in Donggala Regency from 2020 to 2024. This study employed an observational analytic design with a case–control approach, involving a total sample of 108 subjects, consisting of 54 cases and 54 controls, selected using purposive sampling. Secondary data were obtained from Maternal Verbal Autopsy (MVA) records and the maternal cohort registry. Data analysis was conducted using IBM SPSS Statistics, applying Odds Ratio (OR) and p-values for bivariate analysis, and multiple logistic regression for multivariate analysis. The results of the study showed that the risk factors for maternal mortality in Donggala Regency during 2020–2024 were a history of hemorrhage (AOR = 9.01; 95% CI = 1.61–50.64; p = 0.013), history of disease (AOR = 8.21; 95% CI = 1.56–43.32; p = 0.013), and incomplete antenatal care (ANC) visits (AOR = 6.14; 95% CI = 1.52–24.85; p = 0.011). Delay in referral was identified as the main and independent risk factor associated with maternal mortality (AOR = 10.05; 95% CI = 2.04–49.61; p = 0.005). Parity, interpregnancy interval, history of hypertensive disorders of pregnancy, and maternal education did not show statistically significant associations; however, they acted as confounding variables in the final multivariate model.Maternal mortality in Donggala District during 2020–2024 was significantly influenced by a history of hemorrhage, comorbid diseases, inadequate ANC, and referral delay. Referral delay was the strongest determinant of maternal mortality. These findings highlight the importance of early detection of pregnancy complications, adherence to standard ANC services, and an effective and timely maternal referral system to reduce maternal mortality